Pseudolamproglena boxshalli sp. n. (Lernaeidae: Lamprogleninae) parasitic on gills of Cyprinion macrostomum (Teleostei: Cyprinidae) from the Tigris River, Iraq - Al-Nasiri, Fatima S; Ho, Ju-Shey; Mhaisen, Furhan T (Folia parasitologica, 2012)
Abstract: A new species of lamproglenine copepods, Pseudolamproglena boxshalli sp. n., is described from gills of the cyprinid fish Cyprinion macrostomum Heckel from the Tigris River in Tikreet, north of Baghdad, Iraq. This is the second species of Pseudolamproglena from Iraq and the fourth in the world. It differs from its three congeners mainly in the armature ofantennule, maxilla, maxilliped, legs 1-4 and caudal ramus.
Keywords: Cyprinidae; Fish Diseases; korýši; zvířata; Crustacea; Iraq; řeky; nemoci ryb; Animals; Gills; Irák; Rivers; žábry